Conditions contributing to the incidence of floor eggs in commercial cage-free egg production in Australia - Claudia Ciarelli; Peter J. Groves; Wendy I. Muir (Journal of Applied Poultry Research)
SUMMARY: Commercial laying hens have been housed in conventional caged systems in Australia for many years where they have achieved maximum production through close management of temperature, lighting, diet, waste removal, automated egg collection, and secure food safety. However, the birds were limited in expressing natural behaviors including perching, nesting, and dust bathing. Increased public awareness of hen welfare prompted a shift in the housing type and there is now a predominance of cage-free housing including barn and free-range systems in Australia. In these houses the designated egg laying nesting areas are included in the indoor area and are designed to keep eggs clean while facilitating automatic egg collection. However, some hens choose to lay their eggs outside of the designated nesting areas. These eggs, referred to as mislaid, ground or floor eggs, cost the farming operation as they must be collected manually and are downgraded. This study was an opportunistic investigation into the putative risk factors for floor eggs from 69 commercial Australian brown egg-laying flocks. Two contexts of floor egg production were evaluated: where the farmer was concerned with the level of floor eggs or, where floor eggs were ≥2% production at peak lay. Flocks housed with cool white lighting or, that had experienced feather pecking, were associated with the farmer being concerned with the level of floor eggs. One strain of brown egg-layer contributed to ≥2% floor eggs at peak lay. These findings can assist farmers with operational decisions to minimize the number of floor eggs.